Physical and Corrosion Properties of CoCrNi Medium Entropy Alloy Thin Films - Mohamed, Omer Fathalrahman (2021)
A Master of Science thesis in Mechanical Engineering by Omer Fathalrahman Mohamed entitled, “Physical and Corrosion Properties of CoCrNi Medium Entropy Alloy Thin Films”, submitted in November 2021. Thesis advisor is Dr. Wael Abuzaid and thesis co-advisor is Dr. Mehmet Egilmez. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).